Under Pressure: The Effect of Antioxidants on Health Consequences Related to Oxidative Stress. (January 2021) - Patel, Pankaj C.; Wolfe, Marcus T.
We examine the relationships between oxidative stress (i.e., manifestations of physiological stress), antioxidants, potentially negative health outcomes (i.e., triglyceride levels), and self-employment through two studies. Our results indicate that oxidative stress is associated with higher triglyceride levels and, as hypothesized, this relationship is mitigated in the presence of higher levels of antioxidants. Perhaps most interestingly, in both studies, we find that oxidative stress has a stronger positive relationship with triglyceride levels for individuals who are self-employed and have lower antioxidant levels relative to employed individuals. We discuss the implications of these findings on research regarding self-employment, stress, and well-being.